(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lakitan B, Kartika, Susilawati, Wijaya A. 2021. Acclimating leaf celery plant (Apium graveolens) via bottom wet culture to increase its adaptability to the tropical riparian wetland ecosystem. Biodiversitas 22: 320-328. Bottom-wet culture was set up for acclimating leaf celery plant prior to cultivation at shallow water table conditions. The aim of this research was to evaluate adaptability of leaf celery plants to riparian wetland ecosystem. Leaf celery was selected as potential candidate since natural habitat of its wild relatives is marshlands. Shading at 0%, 20%, and 60% was applied to reduced tropical sunlight intensity. Results of this study indicated that soil moisture was significantly increased in plants exposed to 60% shading, but leaf SPAD value was not significantly affected. Leaf celery is a perennial vegetable that can be frequently harvested. Weekly harvesting was rewarded with optimum yield and good quality leaves, i.e. high SPAD value (45.73 to 51.89). Delaying harvest to 3 weeks increased total yield but 52.12% of the harvested leaves were non-marketable. Mother plant of leaf celery produced suckers, but number of suckers only moderately correlated with yield (R2 = 0.56). Plants exposed to 60% shading produced significantly less suckers (9.00) than those exposed to full sunlight (12.46) and 20% shading (12.88) Use of zero intercept linear regression model, with length of leaf midrib (LLM) x leaf wingspan (LWS) as predictor, resulted in a geometrically based and accurate leaf area estimation model (LA = 0.3431(LLM x LWS); R2 = 0.87) for compound leaves of leaf celery plant. In conclusion, the most crucial factor in optimizing quantity and quality of yield was weekly harvesting focusing on marketable-size leaves.